Removal of Common Bile Ducts Stones via Percutaneous Access with a Flexible Ureteroscope and Laser Assistance. (15th October 2019) - Loffeld, R. J. L. F.; Paulus, J.; Langbein, S.; Jansen, B.
Abstract : Two patients are described with large stones in the common bile duct. Standard ERCP was not possible. Both patients were successfully treated with percutaneous access and use of the ureteroscope with the holmium laser.